Tahapan Implementasi P5 di SMA NEGERI 2 GORONTALO: Tahapan Implementasi P5 di SMA NEGERI 2 GORONTALO - Zihan Usman; Meilan Matiti; Imam Mashudi (Jurnal Ilmu Pendidikan dan Budaya, 2022)
SMA Negeri 2 Gorontalo is one of the schools in the city of Gorontalo, precisely on Jalan Rambutan, Buladu, Kota Barat District. With a total of approximately 1400 students, with around 87 teaching staff. This research was conducted to find out about the stages of implementation of the Pancasila Student Profile Strengthening Project (P5) at SMA Negeri 2 Gorontalo. This study uses a qualitative method. The research results were obtained from interviews. The results of the interviews showed that the implementation stages of the Pancasila Student Profile Strengthening Project (P5) went smoothly and effectively. This learning stage has been carried out and carried out in grades 10 and 11 while grade 12 has not yet because this class is an exam class so that adjustments are experiencing obstacles. In addition, the activities of the Pancasila Student Profile Strengthening Project (P5) are also very helpful for teachers and students in the learning process. The objective of the implementation of the Pancasila Student Profile Strengthening Project (P5) is to train students to become superior and productive learners. The Pancasila Student Profile Strengthening Project is one part of the implementation of the independent curriculum. P5 implementation activities are carried out based on stages, where the stages are divided into 4, namely: 1.) Introduction, 2.) Exploratory activities, 3.) Action learning, 4) Results. One of the P5 activities carried out at SMA Negeri 2 Gorontalo was Tuja'I where Tuja'I is one of Gorontalo's traditions that must be known by the people of Gorontalo, especially the nation's next generation.